Holocene fluviatile processes and valley history in the river Rhine catchment - Schirmer, Wolfgang; Bos, Johanna A. A.; Dambeck, Rainer; Hinderer, Matthias; Preston, Nick; Schulte, Achim; Schwalb, Antje; Wessels, Martin (ERDKUNDE, 2005)
A detailed investigation of the River Rhine catchment resulted in a system of the fluvial facies (the “fluvial series”), the structure and the texture of fluviatile terrace bodies and different terrace patterns. The valley bottom is formed by ten fluvial accumulation phases, three of upper Würmian age and seven of Holocene age. Synchronous phases of alternating increased fluvial activity and quiescence on major and smaller rivers give proof of climatic control over the fluvial rhythmicity. The quiescence phases are not only marked by a retreat of the river sedimentation but also by fossil soils that are separating floodloam veneers of the individual fluviatile series. Local forming of the valley ground by the individual river catchment does affect the texture, pattern, structure and floodplain soil types of the terrace sequences. Man’s impact since the Neolithic Period modifies increasingly the natural valley-forming processes: input of fines into the floodplain since the Atlantic period, essential widening of the floodplain since the beginning of the Subatlantic period, flattening of the channel with a tendency to braiding since the early Middle Ages, canalising of the channel and remodelling of the floodplain since the course of the 19th century. But despite human modification, the natural imprints are dominating and remain visible. A first small onset of budgeting of the sediment flux rates of parts of the three periods, the glacial, the natural Holocene and the human Holocene periods, is shown by three case studies still rather restricted in space and resolution of time: the Rhine delta within the Lake Constance, the Elsenz catchment as Neckar tributary close to Heidelberg and a versant area in the Siebengebirge directed towards the River Rhine.